2009
DOI: 10.1128/aem.02660-08
|View full text |Cite
|
Sign up to set email alerts
|

High Rate of N 2 Fixation by East Siberian Cryophilic Soil Bacteria as Determined by Measuring Acetylene Reduction in Nitrogen-Poor Medium Solidified with Gellan Gum

Abstract: For evaluating N 2 fixation of diazotrophic bacteria, nitrogen-poor liquid media supplemented with at least 0.5% sugar and 0.2% agar are widely used for acetylene reduction assays. In such a soft gel medium, however, many N 2 -fixing soil bacteria generally show only trace acetylene reduction activity. Here, we report that use of a N 2 fixation medium solidified with gellan gum instead of agar promoted growth of some gellan-preferring soil bacteria. In a soft gel medium solidified with 0.3% gellan gum under ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(69 citation statements)
references
References 42 publications
0
69
0
Order By: Relevance
“…In contrast to the molecular assessment results, only 39% of isolates displayed acetylene reduction activity. Previously, it has been reported that the N 2 -fixing ability of the different diazotrophs varied depending upon a number of factors, such as incubation time and temperature, growth medium, O 2 concentration, and type of solidifying agent (7,8,14,21,24,26). Therefore, it is likely that the absence of nitrogenase activity can be attributed to the experimental conditions used in this study.…”
Section: Figmentioning
confidence: 70%
See 2 more Smart Citations
“…In contrast to the molecular assessment results, only 39% of isolates displayed acetylene reduction activity. Previously, it has been reported that the N 2 -fixing ability of the different diazotrophs varied depending upon a number of factors, such as incubation time and temperature, growth medium, O 2 concentration, and type of solidifying agent (7,8,14,21,24,26). Therefore, it is likely that the absence of nitrogenase activity can be attributed to the experimental conditions used in this study.…”
Section: Figmentioning
confidence: 70%
“…4) highlights the potential bias that might occur during attempts to isolate N 2 fixers using traditional methods, regardless of their dominance in the environment. Previously, Hara and coworkers (21) reported that 80 to 100% of the N 2 -fixing isolates from surface and subsurface soil samples from a Siberian forest belonged to the genus Pseudomonas. We reason that the high dominance of this group might be associated with the use of a semisolid N-free medium.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Photosynthesis constitutes the more abundant source of energy in tundra compared to easily decomposable organic compounds and therefore the majority of studies on N 2 fixation in high-latitude ecosystems are focused on autotrophic N 2 fixation by cyanobacteria (Liengen and Olsen, 1997;Liengen, 1999b;Solheim et al, 2002;Sorensen et al, 2006;Stewart et al, 2011a), while the contribution of heterotrophic bacteria has been considered insignificant. However, recent studies presented evidence that also diazotrophic soil bacteria can substantially contribute to the local soil N pool by fixing atmospheric N 2 (Nosko et al, 1994;Hara et al, 2009;Zadorina et al, 2009). As such, there is a paucity of studies on N 2 fixation in highlatitude ecosystems and our understanding of the role of diazotrophs for N budgets in tundra is poor.…”
Section: Introductionmentioning
confidence: 99%
“…Culture Media: Preparation of Winogradsky's N-free medium referred to Hara's method, N-free plates with 1.6% agar [14].…”
Section: A Materials and Mediummentioning
confidence: 99%